WHAT KNOWLEDGE DO MATHEMATICS TEACHERS DEVELOP DURING THE LESSON STUDY PRACTICE? A CASE STUDY FROM SECONDARY SCHOOL - Aini Haziah Binti Amirullah; Fitriati Fitriati; Roslinda Rosli (Jurnal Numeracy, 2025)
Understanding what knowledge mathematics teachers develop during lesson study is crucial for improving teaching practices and student learning outcomes. Despite widespread use of lesson study as a professional development approach, limited research has explored the specific types of teacher knowledge that emerge through this collaborative process, especially in secondary education contexts. This study explores the types of knowledge developed by mathematics teachers during the implementation of Lesson Study. Using a qualitative case study design, data were collected from three Lesson Study cycles involving four junior secondary school mathematics teachers. Data sources included classroom observations, video recordings of planning and reflection sessions, and teaching documents. Transcript-based lesson analysis was employed to examine changes in teachers’ knowledge across three key domains: mathematical content knowledge, pedagogical content knowledge (PCK), and awareness of student thinking. Findings indicate that participation in Lesson Study encouraged deeper conceptual understanding, more deliberate instructional decisions, and greater sensitivity to students’ learning processes and misconceptions. These outcomes highlight the transformative potential of Lesson Study in fostering collaborative, practice-based professional growth. The study concludes by recommending the strengthening of school–university partnerships and the institutionalization of Lesson Study as an effective and context-responsive approach to mathematics teacher development in Indonesia.